2020
DOI: 10.1534/g3.120.401596
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Transposable Elements Following a Shared Polyploidization Event in the Tribe Andropogoneae

Abstract: Both polyploidization and transposable element (TE) activity are known to be major drivers of plant genome evolution. Here, we utilize the Zea-Tripsacum clade to investigate TE activity and accumulation after a shared polyploidization event. Comparisons of TE evolutionary dynamics in various Zea and Tripsacum species, in addition to two closely related diploid species, Urelytrum digitatum and Sorghum bicolor, revealed variation in repeat content among all taxa included in the study. The repeat composition of U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The activation of retrotransposons in response to stressors and extreme change is common in eukaryotes 25 27 . In grasses, it has been observed that Copia transposable elements are more frequently inserted near genes associated with stress response 28 . Similarly, in pitaya plants and Dendrobium officinale , Copia retrotransposons exhibit transcriptional activation, and among environmental stressors, transcriptional activation was highest in response to cold stress in particular 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of retrotransposons in response to stressors and extreme change is common in eukaryotes 25 27 . In grasses, it has been observed that Copia transposable elements are more frequently inserted near genes associated with stress response 28 . Similarly, in pitaya plants and Dendrobium officinale , Copia retrotransposons exhibit transcriptional activation, and among environmental stressors, transcriptional activation was highest in response to cold stress in particular 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the repressive chromatin modifications mediated by RNA-directed DNA methylation, LTR retrotransposon activity is typically epigenetically silenced. However, under certain biotic and abiotic phenomena, host repression might fail, resulting in large-scale LTR retrotransposon activation and/or proliferation [ 22 , 23 ]. Recent studies have provided valuable insights into LTR retrotransposon dynamics in allopolyploids between distantly related genomes, which might be restricted to some specific elements and/or model systems.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, genome-sized polymorphisms might re ect the activity of retrotransposons, particularly the copy number differences among long terminal repeat (LTR) retrotransposons, which can achieve exceptionally high copy numbers and often occupy over 50% of the nuclear DNA content, although these elements are typically transcriptionally silent [17]. Ty1copia and Ty3-gypsy elements represent two major superfamilies of LTR retrotransposons in plants with similar structural features, e.g., anking LTRs in direct orientation and multiple domains involved in different steps of element transposition [18]. The LTR retrotransposon replication cycle involves mobilization via a reverse transcriptase (RT)mediated copy-and-paste mechanism, whereby individual elements serve as transcriptional templates for the synthesis of mRNAs, which are reverse transcribed prior to integration at new positions as double-stranded DNA molecules [17].…”
Section: Introductionmentioning
confidence: 99%